2021
DOI: 10.1007/s00277-021-04565-1
|View full text |Cite|
|
Sign up to set email alerts
|

Allogeneic hematopoietic stem cell transplantation improves long-term outcome for relapsed AML patients across all ages: results from two East German Study Group Hematology and Oncology (OSHO) trials

Abstract: SummaryRelapse of acute leukemia is a frequent complication with uncertain outcome and poorly defined risk factors. From 1621 patients entered into two prospective clinical trials (AML02; n = 740 and AML04; n = 881), 74.2% reached complete remission (CR) 1 after induction(s) and 59 patients after additional induction ± hematopoietic cell transplantation (HCT). Of the non-refractory patients, 48.4% with a median age of 63 (range 17–85) years relapsed. Relapses occurred within 6 months after CR in 46.5%, between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Acute myeloid leukemia (AML) remains a fatal disease with only around 10–15% long-term survival in patients older than 60 years [ 1 , 2 ]. For eligible patients, the standard treatment is based on intensive chemotherapy and has hardly changed throughout the last decades.…”
Section: Introductionmentioning
confidence: 99%
“…Acute myeloid leukemia (AML) remains a fatal disease with only around 10–15% long-term survival in patients older than 60 years [ 1 , 2 ]. For eligible patients, the standard treatment is based on intensive chemotherapy and has hardly changed throughout the last decades.…”
Section: Introductionmentioning
confidence: 99%
“…(10) Survival outcomes for allogeneic HCT in acute leukemia continue to improve, as studies primarily in leukemia have shown improvement in survival outcomes, with notable decreases in non-relapse mortality over time. (3)(4)(5)20, 21) Thus, allogeneic HCT has become the standard of care in many patients with leukemia especially in diseases with high relapse risk including older patients (22,23) Allogeneic HCT for nonmalignant disease, including hereditary disease in pediatric patients, showed a more than two-fold increase in this decade.…”
Section: Discussionmentioning
confidence: 99%
“…The Delphi process facilitated broad consensus by involving all panel members in round 2, promoting honest opinions through anonymous surveys and allowing members to justify disagreements through discussions. Despite the process's efficiency, time-saving benefits, and potential for reducing biases, 27 the study identified seven statements requiring clarification because of receiving no votes. While the Delphi technique complements other methods, it may not capture diverse perspectives on AML topics.…”
Section: Discussionmentioning
confidence: 99%